Enhancement of bradykinin-induced relaxation by focal brain ischemia in the rat middle cerebral artery: Receptor expression upregulation and activation of multiple pathways. - Youhai Li; Natalia Lapina; Nina Weinzierl; Lothar Schilling (PLoS ONE)
Focal brain ischemia markedly affects cerebrovascular reactivity. So far, these changes have mainly been related to alterations in the level of smooth muscle cell function while alterations of the endothelial lining have not yet been studied in detail. We have, therefore, investigated the effects of ischemia/reperfusion injury on bradykinin (BK)-induced relaxation since BK is an important mediator of tissue inflammation and affects vascular function in an endothelium-dependent manner. Focal brain ischemia was induced in rats by endovascular filament occlusion (2h) of the middle cerebral artery (MCA). After 22h reperfusion, both MCAs were harvested and the response to BK studied in organ bath experiments. Expression of the BK receptor subtypes 1 and 2 (B1, B2) was determined by real-time semi-quantitative RT-qPCR methodology, and whole mount immunofluorescence staining was performed to show the B2 receptor protein expression. In control animals, BK did not induce significant vasomotor effects despite a functionally intact endothelium and robust expression of B2 mRNA. After ischemia/reperfusion injury, BK induced a concentration-related sustained relaxation in all arteries studied, more pronounced in the ipsilateral than in the contralateral MCA. The B2 mRNA was significantly upregulated and the B1 mRNA displayed de novo expression, again more pronounced ipsi- than contralaterally. Endothelial cells displaying B2 receptor immunofluorescence were observed scattered or clustered in previously occluded MCAs. Relaxation to BK was mediated by B2 receptor activation, abolished after endothelium denudation, and largely diminished by blocking nitric oxide (NO) release or soluble guanylyl cyclase activity. Relaxation to BK was partially inhibited by charybdotoxin (ChTx), but not apamin or iberiotoxin suggesting activation of an endothelium-dependent hyperpolarization pathway. When the NO-cGMP pathway was blocked, BK induced a transient relaxation which was suppressed by ChTx. After ischemia/reperfusion injury BK elicits endothelium-dependent relaxation which was not detectable in control MCAs. This gain of function is mediated by B2 receptor activation and involves the release of NO and activation of an endothelium-dependent hyperpolarization. It goes along with increased B2 mRNA and protein expression, leaving the functional role of the de novo B1 receptor expression still open.